2005
DOI: 10.1097/01.sap.0000157901.57961.3b
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Conservation Techniques in Craniofacial Surgery

Abstract: Attempts at reducing exposure to allogeneic transfusions, using blood conservation techniques such as controlled hypotension and normovolemic hemodilution, have met with mixed results and are not always practical in small infants. Recombinant human erythropoietin (RHE), a hormone that stimulates RBC production, increases the hematocrit when administered to infants. A retrospective chart review of all patients undergoing fronto-orbital advancement for craniosynostosis by the same plastic surgeon between January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 19 publications
1
31
0
4
Order By: Relevance
“…Five out of the16 infants in the study group required homologous transfusion, while 7 out of 9 infants in the control group (no treatment) received homologous transfusion. In a similar retrospective study, Meara and colleagues [47] found that transfusion requirements were lower in the study group that received recombinant human erythropoietin and iron in conjunction with other blood conserving modalities (ANH, hypervolemic hemodilution, controlled hypotension) versus the control group, that was not pretreated with erythropoietin but was managed with blood conserving techniques. The investigators concluded that erythropoietin pretreatment combined with blood-conservation modalities was associated with a decreased need for blood transfusion.…”
Section: Combination Of Blood Sparing Modalitiesmentioning
confidence: 99%
“…Five out of the16 infants in the study group required homologous transfusion, while 7 out of 9 infants in the control group (no treatment) received homologous transfusion. In a similar retrospective study, Meara and colleagues [47] found that transfusion requirements were lower in the study group that received recombinant human erythropoietin and iron in conjunction with other blood conserving modalities (ANH, hypervolemic hemodilution, controlled hypotension) versus the control group, that was not pretreated with erythropoietin but was managed with blood conserving techniques. The investigators concluded that erythropoietin pretreatment combined with blood-conservation modalities was associated with a decreased need for blood transfusion.…”
Section: Combination Of Blood Sparing Modalitiesmentioning
confidence: 99%
“…Historically, these procedures carried a high risk for significant blood loss, and the majority of infants who underwent craniosynostosis surgery required transfusions. 8,23,34 Several techniques have been described in the literature, including strip craniectomy, in which brain growth assists in the remodeling of the skull shape (passive remodeling); extensive reconstructive craniectomies including bony repositioning and fixation to immediately correct the skull contour; and more recently, endoscopic approaches followed by postoperative helmeting. For the purposes of this study, only patients treated with an open approach were included.…”
Section: Discussionmentioning
confidence: 99%
“…В исследовании J. G. Meara и соавт., выполненном на базе детской больницы (Мельбурн, Австралия), было установлено, что гемотрансфузия у детей, перенесших эндоскопическую коррекцию НеКС, потребовалась 50% пациентов, получавших эритропоэтин и препарат железа, и всем детям контрольной группы [41].…”
Section: педиатрическая фармакологияunclassified
“…В ряде других исследований авторы пришли к ана-логичным выводам, сводящимся к тому, что предопе-рационное применение эритропоэтина с препаратами железа в сочетании с нормоволемической гемодилюци-ей у детей, перенесших хирургическую коррекцию НеКС, повышает концентрацию гемоглобина и тем самым сни-жает потребность в гемотрансфузиях вдвое [39][40][41]. Наряду с этим также отмечено снижение продолжи-тельности пребывания пациента в стационаре, хотя это и не являлось основной целью исследований [42][43][44].…”
Section: педиатрическая фармакологияunclassified